Framings - Kacunko, Slavko; Harlizius-Klück, Ellen; Körner, Hans (Logos, 2015)
"This volume offers an authoritative and comprehensive insight into the recent enquiry into the frames and framings. It showcases the broad range of the research topics and makes it available for the first time in English. ''Framings'' was the title of a conference held in Copenhagen from 29th November to 2nd December 2013, organized as a joint venture between the Department of Art History at the University of Düsseldorf and the DNRF's Centre for Textile Research, as well as the Department of Arts and Cultural Studies (IKK), University of Copenhagen. Its aim was to bring together strands of pioneering international research on frames that have developed over the past decades. The twenty-two essays provide new insights into a research field which has been rather neglected in spite of its high relevance and topicality. The outline of the volume shows different perspectives and the conceptual frameworks of the conference divided in four sections (Frames: Discreteness, Boundary, Exclusiveness; Frameworks: Medium, Continuity, Performativity; Framings: Visuality, Spatiality, Temporality and Methodological Margins and Cultural [B]Orders). It also reveals the genealogy of the research topic, related not least to the sites, in which the major research initiatives of the recent years have taken place: Düsseldorf and Copenhagen. The contributions originate from the visual and cultural studies, film theory and semiotics, computer science, communication science, art history, media history and theory, literary studies, philosophy and textile science. The essays stem from both senior and emerging researchers from Belgium, Denmark, Germany, Italy, France, Great Britain, Portugal, Switzerland, the Czech Republic, Turkey and the United States."--